Investigation of Antibody Levels During Three Doses of Sinopharm/BBIBP Vaccine Inoculation - Ma, Jing; Cheng, Zhangkai J.; Xue, Mingshan; Huang, Huimin; Li, Shiyun; Fang, Yanting; Zeng, Yifeng; Lin, Runpei; Liang, Zhiman; Liang, Huan; Deng, Yijun; Cheng, Yuanyi; et al. (Frontiers in Immunology, 2022)
Levels of neutralizing antibodies (NAb) after vaccine against coronavirus disease 2019 (COVID-19) can be detected using a variety of methods. A critical challenge is how to apply simple and accurate methods to assess vaccine effect. In a population inoculated with three doses of the inactivated Sinopharm/BBIBP vaccine, we assessed the performance of chemiluminescent immunoassay (CLIA) in its implementation to detect severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) specific antibodies, as well as the antibody kinetics of healthcare workers throughout the course of vaccination. The antibody levels of NAb, the receptor-binding-domain (RBD) antibodies and IgG peaked one month after the second and remained at a relatively high level for over three months after the booster injection, while IgM and IgA levels remained consistently low throughout the course of vaccination. The production of high-level neutralizing antibodies is more likely when the inoculation interval between the first two doses is within the range of one to two months, and that between the first and booster dose is within 230 days. CLIA showed excellent consistency and correlation between NAb, RBD, and IgG antibodies with the cytopathic effect (CPE) conventional virus neutralization test (VNT). Receiver operating characteristic (ROC) analysis revealed that the optimal cut-off levels of NAb, RBD, and IgG were 61.77 AU/ml, 37.86 AU/ml, and 4.64 AU/ml, with sensitivity of 0.833, 0.796, and 0.944, and specificity of 0.768, 0.750, and 0.625, respectively, which can be utilized as reliable indicators of COVID-19 vaccination immunity detection.